Respuesta :

Answer:

Please see detailed solution below.

Step-by-step explanation:

28.) Given the following facts:

GH bisects < FGI  

m < FGH = (3x - 3)°

m <HGI = (4x - 14)°

Since < FGH and < HGI are adjacent angles that have the same vertex, point G:

We can use the Angle Addition Postulate which states that if point G lies in the interior of < FGI then m < FGH + m < HGI = m < FGI.  

Essentially, the Angle Addition Postulate implies that the sum of the parts equal the whole.

To find the measure of < FGI:

Establish the following equality statement:

m < FGH = m < HGI

Substitute the given values into the equality statement:

(3x - 3)° = (4x - 14)°

Combine like terms:

   3x - 3 = 4x - 14

Subtract 3x from both sides:

3x - 3x - 3 = 4x - 3x - 14

           - 3 = x - 14

Add 4 to both sides:

14 - 3 = x - 14 + 14

     11 = x

Now that we have the value for x, substitute 11 into the sum of the given values for < FGH and < HGI to solve for m < FGI:

m < FGH + m < HGI = m < FGI

(3x - 3)° +  (4x - 14)°= m < FGI

[3(11) - 3]° + [4(11) - 14]° = m < FGI

(33 - 3)° + (44 -14)° = m < FGI

30° + 30° = m < FGI

60° = m < FGI

Therefore:

a.) x = 11;   m < FGH = 30°

b.) m < HGI = 30°

c.) m < FGI = 60°

29.) BD Bisects <ABC.  

Given that m < ABD = 5x, and m < DBC = 3x + 10:

Applying the Angle Addition Postulate:

m < ABD +  m < DBC = m < ABC

Using the same method of solving for the value of x earlier:

m < ABD = m < DBC  

5x = 3x + 10  

Subtract 3x from both sides:

5x - 3x = 3x - 3x + 10  

2x = 10

Divide both sides by 2 to solve for x:

2x/2 = 10/2

x = 5

Substitute the value of x to find the value of m < ABC:

m < ABD +  m < DBC = m < ABC

5x + 3x + 10 = m < ABC

5(5) + [3(5) + 10] = m < ABC

25 + (15 + 10) = m < ABC

25 + 25 = m < ABC

x = 5

m < ABC = 50

m < ABD = 25

m < DBC = 25

30) BD Bisects <ABC.  

Given that m < ABC = 4x - 12, and m < ABD = 24

Doing the two other given problems, we can assume that m < ABD is equal to m < DBC, and their sum is equal to m < ABC.  

Since we're already given the value for m < ABD, then it also means that m < DBC = 24.

Applying the Angle Addition Postulate:

m < ABD +  m < DBC = m < ABC

24 + 24 = 4x - 12

48 = 4x - 12

Add 12 to both sides:

48 + 12 = 4x - 12 + 12

60 = 4x

Divide both sides by 4:

60/4 = 4x/4

15 = x

Substitute x into m < ABC to find its measure:

m < ABC = 4x - 12

m < ABC = 4(15) - 12

m < ABC = 60 - 12

m < ABC = 48

x = 15

This proves my statements earlier how the Angle Addition Postulate applies all of the given problems for this post.  

I'd greatly appreciate it if you could please mark my answers as the Brainliest, if you find my thorough explanations and solutions helpful :)